2010
DOI: 10.1016/j.expneurol.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen effects on pain sensitivity and neuropeptide expression in rat sensory neurons

Abstract: While a number of chronic pain conditions are much more prevalent in women than men, the role of estrogen in regulating nociception remains unclear. Estrogen receptors (ER) are known to be expressed in various parts of the nociceptive pathway, including in the small-sized primary sensory neurons of the dorsal root ganglion (DRG). This study evaluated the effects of long-term estrogen replacement on pain sensitivity and neuropeptide expression in the DRG of female Sprague Dawley rats. The goal was to evaluate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Furthermore, several previous studies have established the ability of estradiol exposure to produce facial and peripheral allodynia in animal models. Importantly, our model demonstrates recruitment of similar downstream mechanisms of inflammation (Liverman, 2007), and vasodilation (Sarajari and Oblinger, 2010) exhibited in other work, indicating that our model causes similar results of facial allodynia following treatment with estradiol.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, several previous studies have established the ability of estradiol exposure to produce facial and peripheral allodynia in animal models. Importantly, our model demonstrates recruitment of similar downstream mechanisms of inflammation (Liverman, 2007), and vasodilation (Sarajari and Oblinger, 2010) exhibited in other work, indicating that our model causes similar results of facial allodynia following treatment with estradiol.…”
Section: Discussionsupporting
confidence: 80%
“…It is established that estradiol receptors are present in trigeminal nociceptors and studies have demonstrated that binding of estradiol leads to downstream activation of extracellular signal regulated kinase (ERK), a known inflammatory response pathway (Liverman, et al, 2009). Furthermore, it has been shown that estradiol exposure can lead to other nociceptive-related downstream effects; including, increased primary neuron activity (Cairns, et al, 2001, Cairns, et al, 2002), increased allodynia (Liverman, et al, 2009), altered sodium gated channel activity (Wang, et al, 2013), and enhanced vasodilation (Levy and Burstein, 2011, Sarajari and Oblinger, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that estrogen depletion leads to hyperalgesia, and estrogen replacement exhibits analgesic effect [8,9,24]. In the present study, we observed significant hyperalgesia to mechanical and thermal stimuli in estrogen deficient rats (group Ovx-1), which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…As the important role of estrogen in regulation of pain has been widely recognized [7], studies have demonstrated that estrogen modulates pain via their effects on the peripheral nervous system (PNS), central nervous system (CNS), skeletal, immune and cardiovascular systems [5]. Mechanical and thermal hyperalgesia have been induced in estrogen deficiency animals, and this hyperalgesia could be alleviated by estradiol replacement [8,9].…”
Section: Introductionmentioning
confidence: 99%